Analysis of teacher needs for team-based project learning with the SETS approach on alternative energy source materials - Fauziyyah, Asri Nur Lathifah; Efendi, Ridwan; Muslim, Muslim (ARKA INSTITUTE, 2024)
Alternative energy sources are one of the materials in physics that are very close to their application in daily life. Awareness of the importance of understanding in the era of rapid technological progress in the concept of alternative energy sources needs to be built with learning that actively involves students, one of which is project-based learning. This study aims to analyze the needs of teachers in the implementation of team-based projects with the Science, Environment, Technology, and Society (SETS) approach on alternative energy source materials, in order to train students' creativity. The method used was a questionnaire and interview involving 38 physics teachers. The results show that teachers need learning that integrates team-based projects with the SETS approach because only 50% of teachers have used project-based learning on alternative energy sources. In addition, 89% of teachers face various obstacles in the implementation of project-based learning, including inadequate time allocation, low critical thinking of students, and poor teacher planning. Based on these findings, it is suggested that there is a need for more comprehensive teacher learning innovations and the preparation of more structured teaching modules. In addition, support from the school in terms of facilities and time management is needed to maximize the effectiveness of team-based project learning with the SETS approach. This effort is expected to improve the quality of learning and students' creativity in understanding alternative energy source materials.